The Baggage Handler : A Novel - Rawlings, David 1971- (Nashville : Thomas Nelson, 2019)
"When David, Gillian, and Michael each take the wrong suitcases from baggage claim, the airline directs them to retrieve their bags at a mysterious facility in a deserted part of the city. There they meet the enigmatic Baggage Handler, who shows them there is more in their baggage than what they have packed, and carrying it with them is slowing them down in ways they can't imagine"--
Includes bibliographical references.
Keywords: Attitude (Psychology) -- Fiction; Change (Psychology) -- Fiction; Parables; Psychological fiction; Christian fiction